Lemmus novosibiricus Vinogradov 1924 - James H. Honacki; Kenneth E. Kinman; James W. Koeppl (Alien Press, Inc. & The Association of Systematics Collections, 1982)
Lemmus novosibiricus Vinogradov, 1924. Nat. Hist., ser. 9, 14: 187. TYPE LOCALITY: U.S. S. R., New Siberian Arch., Kotelnyi Isl. DISTRIBUTION: New Siberian and Lyakhov Isis. (U.S. S.R.). COMMENT: Formerly included in obensis; see Curry-Lindahl, 1980, Der Berglemming Lemmus lemmus, 140 pp.; but also see Sidorowicz, 1964, Acta TherioL, 8:223. Published as part of James H. Honacki, Kenneth E. Kinman & James W. Koeppl, 1982, Order Rodentia (Part 4), pp. 477-504 in Mammal Species of the World (1 st Edition), Lawrence, Kansas, USA :Alien Press, Inc. & The Association of Systematics Collections on page 488, DOI: 10.5281/zenodo.7353034